Protein-Loosing Entropathy Induced by Unique Combination of CMV and HP in an Immunocompetent Patient - S. Chen; G. Lalazar; O. Barak; T. Adar; V. Doviner; M. Mizrahi (Case Reports in Medicine)
Protein-losing gastroenteropathies are characterized by an excessive loss of serum proteins into the gastrointestinal tract, resulting in hypoproteinemia (detected as hypoalbuminemia), edema, and, in some cases, pleural and pericardial effusions. Protein-losing gastroenteropathies can be caused by a diverse group of disorders and should be suspected in a patient with hypoproteinemia in whom other causes, such as malnutrition, proteinuria, and impaired liver protein synthesis, have been excluded. In this paper, we present a case of protein-losing enteropathy in a 22-year-old immunocompetent male with a coinfection of CMV and Hp.